CHARACTER EDUCATION IN STUDENTS' ENGLISH LEARNING AT SD MUHAMMADIYAH BOLIHUWANGGA - Amara, Basri Usman; Saripi, Samid (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
The integration of character education values is not only associated with subjects that are directly related to norms, morals and character. Every subject that students study at school leads to the formation of students' character. This research aims to describe character education in Student English Learning at SD Muhammadiyah Bolihuwangga. Growing and developing character education in English conversation programs is the target of research with careful interviews and observations. The results of the research concluded that: 1) programmed English conversation activities encourage students to have meaningful experiences to be able to express English directly with friends, 2) students have the courage to convey English from the basis of insightful knowledge (vocabulary knowledge) and language expressions English (greeting, self-introduction, daily activities and talking about objects), 3) character education in learning English conversation: students are brave, friendly, curious, help each other, caring and have a social spirit.